(untitled) - Fowler, H. Ramsey (New York, 2007)
The Little, Brown Handbook provides reliable and thorough coverage of such handbook basics as the writing process, grammar, research, and documentation, while also giving detailed discussions of critical reading and writing in academic situations, study skills, argument, using computers and the Internet (for both writing and research), writing in the disciplines, writing for public audiences, and oral presentations.
Keywords: English language,Report writing,Anh ngữ thực hành,Viết báo cáo; Grammar,Ngữ pháp